India - Mattern, Joanne 1963- ([Minneapolis, MN] : Pogo, 2019)
"In this book, readers will learn about the unique and defining features of India. Vibrant, full-color photos and carefully leveled text will engage young readers as they learn more about the key details of the country including geography, climate, culture, and resources. Compelling questions encourage further inquiry"--
"Pogo Books."
Keywords: India -- Juvenile literature